2001
DOI: 10.1063/1.1345806
|View full text |Cite
|
Sign up to set email alerts
|

Formation of shallow acceptor states in the surface region of thin film diamond

Abstract: Considerable interest exists in fabrication of electronic devices from thin film polycrystalline diamond. To date, doping this material to achieve good free carrier concentrations and mobilities at room temperature has proved difficult. In this letter we report low temperature Hall effect measurements made on diamond films subjected to a hydrogenation process, such that the near surface region becomes p type without the addition of conventional dopant atoms. High carrier concentrations and mobilities can be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…p-type doping can be achieved with substitutional incorporation of boron, yielding an activation energy of 0.37 eV and, hence, fewer than 1% of the holes are activated at room temperature. 1 Hydrogen-induced surface conductivity can also be utilized to generate holes with an extremely low activation energy, 2,3 and high-performance devices have been demonstrated using this type of layer. 4,5 n-type doping has been much more elusive, with success in substitutional phosphorus doping achieved by relatively few laboratories; 6 an activation energy of 0.6 eV also makes phosphorus an unsuitable dopant for many applications.…”
mentioning
confidence: 99%
“…p-type doping can be achieved with substitutional incorporation of boron, yielding an activation energy of 0.37 eV and, hence, fewer than 1% of the holes are activated at room temperature. 1 Hydrogen-induced surface conductivity can also be utilized to generate holes with an extremely low activation energy, 2,3 and high-performance devices have been demonstrated using this type of layer. 4,5 n-type doping has been much more elusive, with success in substitutional phosphorus doping achieved by relatively few laboratories; 6 an activation energy of 0.6 eV also makes phosphorus an unsuitable dopant for many applications.…”
mentioning
confidence: 99%
“…Note that the temperature during hydrogenation is a parameter which varies from laboratory to laboratory. Although in most cases temperatures between 750 and 850 C are utilized (for a review see [5]) it has been shown by Williams et al [14] that hydrogenation at 550 C also generates a highly conductive surface layer.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, a single activation energy is rarely observed in the case of surface conductive diamond. 4,20 The room temperature value is among the highest recorded for surface conductive diamond. It can be seen from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when hydrogenated, polycrystalline diamond films should be more resistive in general, and this is borne out in the empirical case. 2,4,18,23,24 Figure 8 demonstrates the reduction in sheet resistivity with substrate thickness. Initially these data are confusing, until one considers the fact that grain size increases with thickness in the case of polycrystalline diamond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation